ONOMASTIKA DI NEGERI HATALAI, KECAMATAN LEITIMUR SELATAN, KOTA AMBON: Onomastic in Negeri Hatalai, South Leitimur District, Ambon City - Widya Sendy Alfons (TOTOBUANG, 2023)
Abstract Folkloreinthedevelopmentofscienceandtechnologymoveswidely.Itsmovementofcanusuallyadd a wealth ofcultural treasures and show more diversity. However, maintaining history as an integral part of folklore is also very important. One way to preserve the late culture can be through onomastic studies. In this research, the theory of onomastic figures out the original name of places in Negeri Hatalai,South Leitimur District, Ambon City. This research aims to find information about the inaugural name of places (complexes), soa names, spring names, and street names in Negeri Hatalai. Based on the fact that these histories have begun to be forgottenand are not even well documented. This research is aqualitative. The method used is descriptive qualitative. The data used are the results of an onomastic study, including the name of places (area of residences), soa names, spring names, and street names through several data collection techniques,such asobservation, interviews, field notes, and documentation. The results of this study are the original of 4 soa name, 20 names of places (area of residence), five springs, and three names of streets Keywords: Folklore, Oral Tradition, Onomastic, toponymy, anthroponymy Â  Abstrak Folklor dalam perkembangan ilmu pengetahuan dan teknologi banyak bergerak dengan leluasa. Pergerakan folklor biasanya dapat menambah khazanah budaya menjadi semakin kaya dan beragam. Namun, menjaga sejarah sebagai bagian yang tidak terpisahkan dari folklor juga sangat penting. Salah satu cara merawat budaya masa lalu dapat melalui kajian onomastika. Pada penelitian ini, kajian onomastika digunakan untuk mengetahui asal usul nama tempat di Negeri Hatalai, Kecamatan Leitimur Selatan, Kota Ambon. Penelitian ini bertujuan menggali informasi tentang asal usul nama tempat (kompleks), nama soa, nama mata air, dan nama jalan di Negeri Hatalai. Hal ini didasari fakta bahwa sejarah-sejarah tersebut sudah mulai terlupakan bahkan tidak terdokumentasikan dengan baik. Penelitian ini merupakan penelitian kualitatif. Metode yang digunakan ialah deskriptif kualitatif. Data yang digunakan untuk kebutuhan analisis, meliputi teknik pengumpulan data, yaitu observasi, wawancara, catatan lapangan, dan dokumentasi. Hasil penelitian ini adalah asal-usul 4 nama soa, 20 nama tempat (komples), 5 nama mata air, dan 3 nama jalan.Kata-kata kunci: Folklor, Tradisi Lisan, Onomastiska, Toponimi, Antroponimi